Rat and fish peripheral blood leukocytes respond distinctively to Anisakis pegreffii (Nematoda, Anisakidae) crude extract - Hrabar, Jerko; Petrić, Mirela; Cavallero, Serena; Salvemini, Marco; D’Amelio, Stefano; Mladineo, Ivona (Frontiers in Cellular and Infection Microbiology, 2022)
Infective third-stage larvae (L3) of the marine nematode Anisakis pegreffii cause inflammation and clinical symptoms in humans, their accidental host, that subside and self-resolve in a couple of weeks after L3 die. To characterise the differences in an early immune response of a marine vs. terrestrial host, we stimulated peripheral blood leukocytes (PBLs) of fish (paratenic host) and rat (accidental, human-model host) with A. pegreffii crude extract and analysed PBL transcriptomes 1 and 12 h post-stimulation. Fish and rat PBLs differentially expressed 712 and 493 transcripts, respectively, between 1 and 12 h post-stimulation (false discovery rate, FDR <0.001, logFC >2). While there was a difference in the highest upregulated transcripts between two time-points, the same Gene Ontologies, biological processes (intracellular signal transduction, DNA-dependent transcription, and DNA-regulated regulation of transcription), and molecular functions (ATP and metal ion binding) were enriched in the two hosts, showing an incrementing dynamic between 1 and 12 h. This suggests that the two distinct hosts employ qualitatively different transcript cascades only to achieve the same effect, at least during an early innate immunity response. Activation of later immunity elements and/or a combination of other host’s intrinsic conditions may contribute to the death of L3 in the terrestrial host.